Evaluasi Penggunaan Tikar Pertumbuhan Sebagai Alat Deteksi Dini Kejadian Stunting pada Baduta di Kabupaten Kulon Progo, Yogyakarta: Evaluation of the Use of Child Length Mat as A Stunting Early Detection Tool on Children Under Two in Kulon Progo Regency, Yogyakarta - Chrisnamurti, Elisabeth Sekar; Kusuma, Mutiara Tirta Prabandari Lintang; Helmyati, Siti (Amerta Nutrition, 2024)
Background: Stunting prevention leads to the initiation of child length mats as an early detection tool and the assignment of human development workers as community initiators. There are differences in policy implementation regarding these innovations, particularly in the use of length mats. Objectives: To evaluate the use of a length mat as a stunting early detection tool on children under two in Kulon Progo Regency. Methods: A qualitative research with a case study approach was conducted in two stunting locus villages in Kulon Progo Regency. Data were collected using key informant in-depth interviews, document analysis, and reflective journals. Respondents were recruited using the maximum variation sampling technique, and data were analyzed using thematic analysis in accordance with the theory of diffusion of innovation. Results: Stakeholder acceptance of the length mat was relatively poor. Factors that influenced its adoption in Kulon Progo regency include the pre-existing situation (lack of accurate instruments to measure child length), the easy use of the length mat, and prescribed training. Whereas, factors affecting its rejection include issues related to its relative advantage and validity. This refusal was caused by suboptimal campaigns and a lack of support from the local government. However, the length mat remains in use following its function as a prerequisite for the village fund disbursement. Conclusions: Suboptimal use of the communication channel to introduce the length mat and lack of support from the local government caused the innovation to fail to diffuse at the district level. Hence, strengthening the campaign and inter-stakeholder communication is necessary to improve acceptance and adherence.